Complicaciones postoperatorias de la colecistectomía laparoscópica en el ecuador. revisión sistemática y metaanálisis. - Brito Falconi, Joshua Xavier (My University, 2024)
Introduction: Laparoscopic cholecystectomy is widely used due to its benefits over open surgery; however, it is not without postoperative complications. Objective: To determine the most frequent postoperative complications of laparoscopic cholecystectomy in Ecuador through a quantitative analysis and compare them with global literature via a documentary review. Methods: A meta-analysis of publications from the period 2019-2024 obtained from institutional repositories and indexed journals in Spanish and English was conducted. Studies describing postoperative complications of patients undergoing laparoscopic cholecystectomy in Ecuador were included. Quantitative analysis was performed using MedCalc software. Results: From 5 records with a total of 1340 individuals, a general complication rate of 6.52% was determined. The most common were surgical site infections (1.401%), biliary tract injuries (1.546%), and abscesses (0.72%). Conclusion: The variability in complication rates was attributed to factors such as regional differences and surgical techniques. The surgeon's expertise and the application of standardized protocols, including measures such as Strasberg's critical view of safety, are essential to minimize complications. Emerging technologies and prophylactic processes improve clinical outcomes.
Introducción: La colecistectomía laparoscópica es ampliamente utilizada por sus beneficios sobre la cirugía abierta, sin embargo, no está exenta de complicaciones postoperatorias. Objetivo: Determinar las complicaciones postoperatorias de la colecistectomía laparoscópica más frecuentes en el Ecuador, a través de un análisis cuantitativo contrastándolas con la literatura mundial mediante una revisión documental. Métodos: Se realizó un metaanálisis de publicaciones del periodo 2019-2024 obtenidas de repositorios institucionales y revistas indexadas en español e inglés. Se incluyeron estudios que describieran complicaciones postoperatorias de pacientes sometidos a colecistectomía laparoscópica en Ecuador. El análisis cuantitativo se realizó con el software MedCalc. Resultados: De 5 registros con un total de 1340 individuos, se determinó una tasa general de complicaciones del 6.52%. Las más comunes fueron la infección del sitio quirúrgico (1.401%), las lesiones de la vía biliar (1.546%) y los abscesos (0.72%). Conclusión: La variabilidad en los porcentajes de complicaciones se atribuyó a factores como diferencias regionales y técnicas quirúrgicas. La pericia del cirujano y la aplicación de protocolos estandarizados que incluyan medidas como la visión crítica de Strasberg son esenciales para minimizar complicaciones. Las tecnologías emergentes y procesos profilácticos mejoran los resultados clínicos.
Keywords: COMPLICACIONES POSTOPERATORIAS; COLECISTECTOMIA; LAPAROSCOPIA